TOWARDS RESILIENT CITIES: BIOMIMETIC STRATEGIES FOR URBAN ADAPTATION - Souheila El Bar; Noureddine Zemmouri; Khaoula Amraoui (International Journal of Innovative Technologies in Social Science, 2024)
Biomimicry, as an evolutionary strategy drawn from nature, has emerged as an essential framework for the built environment within the context of sustainable urban development geared towards resilience. By covering the various aspects of human technology, this inventive concept simplifies design processes in all fields, particularly in architecture. It offers adaptive solutions to emerging urban challenges, by providing engineers, architects and urban planners innovative tools to draw inspiration from natural ecosystems. This paper discusses the fundamental principles of biomimicry and its practical application to architectural design and urban sustainability. It presents a holistic biomimetic methodology that uses living organisms as references to develop effective responses to address the critical effects of climate change and enhance the resilience of urban systems. To this end, the study presents a selection of natural inspirational models, with strategic characteristics suitable for sustainable urban environments design; more adapted to hot and arid climates conditions. Learning from nature, this research highlights the transformative potential of biomimetic approaches to improve the resilience and adaptation in cities. By strengthening the harmony between built environments and natural ecosystems, these strategies make it possible to design cities that are more sustainable, balanced and in symbiosis with their environment.